Efektivitas Kepemimpinan Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru di PAUD Al Ashriyyah Nurul Iman Islamic Boarding School - Sy. Ruqayah Ruqayah; Akhmad Shunhaji; Khasnah Syaidah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The difficulty experienced by the head of PAUD al Ashriyyah Nurul Iman in disciplining teachers and motivating them to comply with the foundation's policies is a problem that must be immediately found a solution. This research uses a qualitative approach, data sources obtained through interviews through zoom applications, documentation, and observation. This article found that PAUD al Ashriyyah Principal Nurul Iman in improving teacher discipline used autocratic style to be the dominant style, not seen other styles played by principals in the leadership model. The principal in improving the work discipline of his teachers does not always run smoothly, the obstacles and obstacles faced include that there are still a few teachers who are late in entering the classroom so that they need very strict supervision and guidance in terms of monitoring during learning hours, besides that there are other teachers in making learning tools so that there needs to be action in giving their assignments, So the principal needs to tell what, how the task in detail should be done. To improve discipline in PAUD al Ashriyyah Nurul Iman, the principal does not play only one leadership style, but uses a democratic leadership style where employees or teachers have high work motivation and high competence abilities, or participatory leadership styles if teachers have low work motivation but high competence abilities